THE ANTIQUE FOUNDATIONS FOR THE UNITY OF EDUCATION - Alexander E Krikunov (Peoples' Friendship University of Russia (RUDN University), 2017)
The author of the paper considers the unity of education as a specific way of existence, blurring the distinction between ontological and anthropological interpretations of education. This approach is supposed to adequately identify the philosophic sense of the category of education without linking it exclusively to the philosophic consideration of educational practice. The author also points out the connection between the ideas of the world unity and of a human being's education as a process of gradual approaching one's true and complete image in the history of European philosophy. Even though the contemporary notion of education is most elaborately presented by classical German philosophers, the author aims to show the prospects of addressing the antique philosophic tradition proposing the first conceptualization of education connected with a special ontological position. The author calls attention to the gradual development of views on the systemic nature of being, linking it to the initial didactic guideline of Greek philosophers. The example of Aristotle's ethics proves the integrity of externally separate ways of making up of a person. The author comes to a conclusion about the necessity of taking the connection of educational concepts and a characteristic tendency to create the philosophic theory of the world, the elements of which are united in an integrated system, into account. In the author's opinion, it will allow to define the real philosophic and pedagogical sense of the revision of the classical philosophic tradition, undertaken by the contemporary philosophy.